2017
DOI: 10.3390/ma10040394
|View full text |Cite
|
Sign up to set email alerts
|

The Results of 45 Years of Atmospheric Corrosion Study in the Czech Republic

Abstract: Atmospheric corrosion poses a significant problem with regard to destruction of various materials, especially metals. Observations made over the past decades suggest that the world’s climate is changing. Besides global warming, there are also changes in other parameters. For example, average annual precipitation increased by nearly 10% over the course of the 20th century. In Europe, the most significant change, from the atmospheric corrosion point of view, was an increase in SO2 pollution in the 1970s through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…In addition, the abutments of bridge No. 1 stand in close proximity to the highway, which makes is somewhat similar to the so-called "tunnel-like conditions" and the associated increased deposition of chlorides on the structure [13][14][15], see Figure 4. …”
Section: Bridge Structures For Experimental Testsmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, the abutments of bridge No. 1 stand in close proximity to the highway, which makes is somewhat similar to the so-called "tunnel-like conditions" and the associated increased deposition of chlorides on the structure [13][14][15], see Figure 4. …”
Section: Bridge Structures For Experimental Testsmentioning
confidence: 91%
“…In addition, the abutments of bridge No. 1 stand in close proximity to the highway, which makes is somewhat similar to the so-called "tunnel-like conditions" and the associated increased deposition of chlorides on the structure [13][14][15], see Figure 4. The general conditions for the development of corrosion products on typical surfaces of the bridge constructions are very similar-the bridges are situated in the same location, with just minimal differences in orientation.…”
Section: Experimental Tests For Monitoring the Development Of Corrosimentioning
confidence: 91%
See 1 more Smart Citation
“…However, the corrosion behaviour of unprotected steel depends on: atmospheric pollution (chloride and sulphur dioxide content, among others), time of wetness (TOW), amount of rainfall, wind speed and direction, angle of exposure and the characteristics of the corrosion product formed. It is therefore important to classify the aggressiveness of the environment at a site where a carbon steel structure is to be installed …”
Section: Introductionmentioning
confidence: 99%
“…Air pollution also affects visibility [17] and materials [18][19] (including historical buildings and monuments) [20][21]. Tidblad et al (2016) showed the results of research on various corroded materials at 10 locations in Kathmandu (Nepal) related to SO 2 , NO 2 , O 3 , HNO 3 , and PM concentrations and climatic factors, and compared the results with a general pattern from exposures at different sites in Asia, Africa, and Europe [20].…”
Section: Ligus Mmentioning
confidence: 99%